Atopic eczema and fracture risk in adults: a population-based cohort study - Lowe, K; Mansfield, K; Delmestri, A; Smeeth, L; Roberts, A; Abuabara, K; Prieto Alhambra, D; Langan, S (Elsevier, 2019)
Background: Limited evidence suggests increased fracture risk in people with atopic eczema. Any link could have substantial effect; atopic eczema is common, and fractures have associated morbidity and mortality.